Central Serous Chorioretinopathy: Treatment with Laser - Maurizio Battaglia Parodi; Alessandro Arrigo; Pierluigi Iacono; Bruno Falcomatà; Francesco Bandello (MDPI AG, 2020)
Currently, no general consensus exists regarding the management of central serous chorioretinopathy (CSC). Laser treatments include three different therapeutic approaches: conventional laser, subthreshold laser and photodynamic therapy. Conventional focal laser, addressed to seal the leaking points, as evidenced on fluorescein angiography, was largely used in the past, but now, it is almost completely abandoned, owing to the potential complications. Several studies confirmed the positive effects achieved by subthreshold laser treatment in CSC, even though its improper application in the PLACE trial has questioned the effectiveness.